Study the effect of ketogenic diet on weight loss and lipid profile on obese rats - Ahmed, Waheeba Elfaki; Al-Meazil, Munirah Suliman; Al-Salamah, Aseel Ali (Journal of medical and pharmaceutical sciences, 2023)
Obesity is defined as a high percentage of body fat, which is frequently associated with a high body mass index (BMI), which links an individual's weight and height. Obesity is a frequent and widespread disease all over the world, affecting both children and adults, male and female. Obesity, as a source of many diseases and health problems, has recently emerged as a severe health issue that necessitates treatment and follow-up. Obesity prevalence in various age groups worldwide, including Saudi Arabia, where the obesity incidence is 59%, and the dangers of obesity-related ailments such as type 2 diabetes, strokes, and heart disease, which leads to Increased medication use with bariatric surgery. The ketogenic diet (KD) has recently become the most popular diet all over the world. As a result, the keto diet comprises eating a lot of fat, a tiny bit of protein, and very little carbohydrates. The goal of this research report is to learn more about the effects of a KD on weight loss and lipid profile. In this study, the qualitative method was applied, which relies on secondary data sources. In this study, we used a range of research that was also conducted by other researchers.
Keywords: ketogenic diet; Obesity; lipid profile; weight loss